Neck treatment compared to aerobic exercise in migraine: A preference-based clinical trial - Kerstin Luedtke; Wiebke Starke; Karolin von Korn; Tibor Maximillian Szikszay; Annika Schwarz; Arne May (SAGE Publishing, 2020)
Objectives: The main objective of this study was to compare the effectiveness of aerobic exercise with physiotherapy. A second objective was to evaluate whether patients with pain referred to the head during manual palpation will benefit more from physiotherapy than patients with local or no pain. Methods: A total of 103 patients with migraine received physiotherapy ( n = 79) or supervised aerobic exercise ( n = 24) according to their preference as an add-on treatment. Both groups had the same contact time with a specialized physiotherapist. The primary outcome measure was headache frequency during the 4 weeks after the intervention. Eighty-seven patients were analyzed at the primary end point ( n = 69 in the physiotherapy group; n = 18 in the aerobic exercise group). A follow-up assessment was conducted 3 months after the final intervention. Results: During the initial assessment of the upper cervical spine, 17 patients reported no pain, 45 local pain, and 25 referred pain to the head. Patients in the physiotherapy group had a mean reduction of 1.8 days (standard deviation (SD) 6.07), while patients in the aerobic exercise group had a mean reduction of 1.2 days (SD 4.27) at the primary end point. This difference was not statistically significant ( p = 0.8). The largest improvement was noted in the group that showed referred pain to the head and received physiotherapy (2.13 days (SD 7.82)). Only patients in the physiotherapy group reported a subjectively perceived general improvement. Conclusions: Patients had a strong preference for physiotherapy. Both groups showed small reductions in headache frequency. Effects were superior after physiotherapy but not statistically significant. Patients with pain referred to the head responded best to a physiotherapy intervention.